2014
DOI: 10.1242/dev.099622
|View full text |Cite
|
Sign up to set email alerts
|

PRDM14 promotes active DNA demethylation through the Ten-eleven translocation (TET)-mediated base excision repair pathway in embryonic stem cells

Abstract: Ten-eleven translocation (TET) proteins oxidize 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC) and 5-carboxylcytosine (5caC). 5fC and 5caC can be excised and repaired by the base excision repair (BER) pathway, implicating 5mC oxidation in active DNA demethylation. Genome-wide DNA methylation is erased in the transition from metastable states to the ground state of embryonic stem cells (ESCs) and in migrating primordial germ cells (PGCs), although some resistant regions become … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 48 publications
2
102
1
Order By: Relevance
“…There is some evidence that Tet2 activity can be enhanced by other factors. For example, it has been reported that PRDM14 induces DNA demethylation at that germlinespecific genes Piwil2 and Slc25a3, meanwhile, PRDM14 can also enhance the binding of Tet2 at or near the TSS of these genes (Okashita et al, 2014). Recent studies have shown that histone H3 peptide induces the activation of de novo DNA methyltransferase by removal of Dnmt3a-mediated autoinhibition, which stimulates a configuration change Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that Tet2 activity can be enhanced by other factors. For example, it has been reported that PRDM14 induces DNA demethylation at that germlinespecific genes Piwil2 and Slc25a3, meanwhile, PRDM14 can also enhance the binding of Tet2 at or near the TSS of these genes (Okashita et al, 2014). Recent studies have shown that histone H3 peptide induces the activation of de novo DNA methyltransferase by removal of Dnmt3a-mediated autoinhibition, which stimulates a configuration change Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…2,41 The transcriptional regulator PRDM14 interacts with TET1 and TET2 and enhances their recruitment to target loci promoting active DNA demethylation in embryonic stem cells. 43 Another example of differential TET interaction is the transcriptional repressor REST that interacts specifically with the neuronal isoform of TET3, but neither with other TET3 nor TET1 or TET2 proteins. 44 In contrast to the moderate TET1 overexpression in our study, Jin and colleagues 30 overexpressed TET1 at very high levels and also identified up-and downregulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TET1-CD-induced demethylation events have a different genomic distribution from those induced by full length TET1 or other TET family members primarily through DNA replication-based passive pathway in the HEK293T cell model, suggesting the predominance of passive pathway in all TET-induced global demethylation processes. By contrast, the reported locus-specific DNA demethylation events were always achieved through active demethylation10,16,32 . Thus, passive and active demethylation pathways selectively function in TET-induced global and locus-specific DNA demethylation.…”
mentioning
confidence: 88%